An Efficient Method for Solving Spread Option Pricing Problem: Numerical Analysis and Computing - R. Company; V. N. Egorova; L. Jódar (Abstract and Applied Analysis)
This paper deals with numerical analysis and computing of spread option pricing problem described by a two-spatial variables partial differential equation. Both European and American cases are treated. Taking advantage of a cross derivative removing technique, an explicit difference scheme is developed retaining the benefits of the one-dimensional finite difference method, preserving positivity, accuracy, and computational time efficiency. Numerical results illustrate the interest of the approach.